Impact of Land Use and Land Use Change on Greenhouse Gas Emissions in Palembang City: Dampak Penggunaan Lahan dan Perubahan Tata Guna Lahan terhadap Emisi Gas Rumah Kaca di Kota Palembang - Alia, Febrinasti; Hadinata, Febrian; Trimahmudi, Arief; Apriani, Nyimas Ida (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
Climate change is mainly anthropogenic mostly caused by urbanization, human activities in economics, industry, and transportation. The expansion of built-up land, deforestation and the loss of farmland are closely linked to land use and land use change. Greenhouse gas emissions produced by the land use sector can significantly affect global carbon budgets by changing the carbon storage level in terrestrial ecosystem vegetation and soil. In 2005, Indonesia was responsible for approximately 85% of carbon emissions. The Indonesian government is combating environmental issues by mandating local governments, including Palembang City, to conduct greenhouse gas inventories. Changes in land use and the amount of carbon stock in Palembang City can be taken into consideration by the Palembang City Government in dealing with climate change. Data analysis was carried out by interpreting satellite imagery SPOT-7 and classification of land use data into six classes based on AFOLU guidelines. The area derived from land use transition matrix of the period 2012-2018 is used as a basis to calculate greenhouse gas emissions. The greenhouse gas emissions were then calculated using the Gain-Loss method based on the IPCC journal as a reference. Due to land use and land use change from 2012 to 2018, Palembang City emits greenhouse gas as much as -149098.5827 Tonnes C/Year in total. Forest Land Category -26557.22425 Tonnes C/Year, Crop Land Category -112739.8894 Tonnes C/Year, Grass Land Category -32257.56413 Tonnes C/Year, Wetland Category -20721.68315 Tonnes C/Year, Settlement Category 43273.249 Tonnes C/Year and Other Land Category -95.4708 Tonnes C/Year. Inventories on greenhouse gas (GHG) emissions and absorption trends are crucial for climate change mitigation strategies in Palembang. One important strategy towards achieving net zero emissions by 2060, as initiated by the Government of Indonesia, is to curb carbon release associated with land use changes.